Scale-up and process integration of sugar production by acidolysis of municipal solid waste/corn stover blends in ionic liquids. Issue 1 (December 2017) - Li, Chenlin; Liang, Ling; Sun, Ning; Thompson, Vicki; Xu, Feng; Narani, Akash; He, Qian; Tanjore, Deepti; Pray, Todd; Simmons, Blake; Singh, Seema
Abstract Background Lignocellulosic biorefineries have tonnage and throughput requirements that must be met year round and there is no single feedstock available in any given region that is capable of meeting the price and availability demands of the biorefineries scheduled for deployment. Significant attention has been historically given to agriculturally derived feedstocks; however, a diverse range of wastes, including municipal solid wastes (MSW), also have the potential to serve as feedstocks for the production of advanced biofuels and have not been extensively studied. In addition, ionic liquid (IL) pretreatment with certain ILs is receiving great interest as a potential process that enables fractionation of a wide range of feedstocks. Acid catalysts have been used previously to hydrolyze polysaccharides into fermentable sugars following IL pretreatment, which could potentially provide a means of liberating fermentable sugars from lignocellulose without the use of costly enzymes. However, successful optimization and scale-up of the one-pot acid-assisted IL deconstruction for further commercialization involve challenges such as reactor compatibility, mixing at high solid loading, sugar recovery, and IL recycling, which have not been effectively resolved during the development stages at bench scale. Results Here, we present the successful scale-up demonstration of the acid-assisted IL deconstruction on feedstock blends of municipal solid wastes and agricultural residues (corn stover) by 30-fold, relative to the bench scale (6 vs 0.2 L), at 10% solid loading. By integrating IL pretreatment and acid hydrolysis with subsequent centrifugation and extraction, the sugar and lignin products can be further recovered efficiently. This scale-up development at Advanced Biofuels/Bioproducts Process Demonstration Unit (ABPDU) will leverage the opportunity and synergistic efforts toward developing a cost-effective IL-based deconstruction technology by drastically eliminating enzyme, reducing water usage, and simplifying the downstream sugar/lignin recovery and IL recycling. Conclusion Results indicate that MSW blends are viable and valuable resource to consider when assessing biomass availability and affordability for lignocellulosic biorefineries. This scale-up evaluation demonstrates that the acid-assisted IL deconstruction technology can be effectively scaled up to larger operations and the current study established the baseline of scaling parameters for this process.